The potential prognostic role of cardiovascular autonomic failure in α‐synucleinopathies. Issue 2 (27th July 2012) - Fanciulli, A.; Strano, S.; Colosimo, C.; Caltagirone, C.; Spalletta, G.; Pontieri, F. E.
Abstract : Cardiovascular autonomic failure is the second most common dysautonomic feature of α‐synucleinopathies and has significant impact on daily activities and quality of life. Here we provide a systematic review of cardiovascular autonomic failure in α‐synucleinopathies, emphasizing its impact on cognitive functions and disease outcomes. Articles spanning the period between January 1985 and April 2012 were identified from the PubMed database using a keyword‐based search. Epidemiological studies highlight the negative prognostic effect of cardiovascular autonomic failure on cardiovascular and cerebrovascular outcomes and overall mortality in all α‐synucleinopathies. Altered cerebral perfusion, vascular pressure stress, and related disruption of the blood–brain barrier may also contribute to the white matter hyperintensities and cognitive dysfunction frequently found in patients affected by neurocardiovascular instability. These findings support the hypothesis that cardiovascular autonomic failure may play a negative prognostic role in α‐synucleinopathies and suggest that precocious screening and therapeutic management of cardiovascular autonomic failure may positively impact disease course.